Redox Dichotomy in Cell Fate Decision: Evasive Mechanism or Achilles Heel? - Pervaiz, Shazib (Mary Ann Liebert, Inc. Publishers, 2018)
© 2018, Mary Ann Liebert, Inc., publishers. Cellular redox state is a consequence of the balance between the rates of reactive oxygen species and/or reactive nitrogen species, and their dissipation via enzymatic and nonenzymatic redox buffering systems. While low levels of oscillation are associated with normal cellular metabolism, stimuli that favor a significant shift in the redox microenvironment, through either the increased production and/or compromise of the antioxidant defenses, induce overt oxidative stress. This change in the redox set point triggers a host of cellular responses ranging from modifications in cellular macromolecules, organelle morphology and physiology, amplified cell-to-cell and intracellular signaling, and changes in genome, epigenome, and proteome. The consequence of this dysregulated cellular homeostasis is therefore manifested in the form of a plethora of pathological states such as inflammation, diabetes mellitus, neurodegenerative disorders, atherosclerosis, and cancer. On the backdrop of these observations, this Forum attempts at reviewing the current understanding of how a prooxidant intracellular milieu favors cell survival while overt oxidative stress results in death execution, and the translation of these biological effects in human disease states, in particular cancer. The far-reaching biochemical, biological, and clinical ramifications of an altered redox environment are also discussed from the standpoint of strategic therapeutic design against refractory and aggressive cancers. It is tempting to conjecture if the inherent or acquired redox heterogeneity, at least in the case of cancer, has evolved as an "evasive mechanism," or presents itself as the "Achilles heel" for therapeutic exploitation.